Framework da influência do choque exógeno na ambidestria organizacional em contexto VUCA e BANI: o papel da TI na percepção de crise e capacidade absortiva - Baptestone, Rolney Carlos (2024)
In a world marked by volatility, uncertainty, complexity, and ambiguity (VUCA), as well as fragility, anxiety, nonlinearity, and incomprehensibility (BANI), organizations face major challenges. This research analyzes the influence of Exogenous Shocks on Organizational Ambidexterity in VUCA and BANI environments and the role of Information Technology (IT) in the Perception of Crisis and in the Absorptive Capacity of organizations, in the face of the shock, to generate a Framework for these relationships. A methodological approach was adopted starting with bibliometrics on the topic Exogenous Shock, to verify the relevance and trends of the topic, followed by a systematic literature review (SLR) to map the state of the art and identify knowledge gaps. Then, a conceptual theoretical model was developed integrating all the constructs of this research. Data were collected through a Survey, applied to a representative sample universe of respondents, with questions seeking answers that would prove or reject the 6 hypotheses (H1 to H6). Next, rigorous statistical analyses were applied, through structural equation modeling, to test the six hypotheses formulated. The results indicated that hypothesis H1 was refuted, showing a significant relationship between Exogenous Shock and Organizational Ambidexterity. Hypothesis H2 was not confirmed, since Exogenous Shocks did not increase Crisis Perception, which invalidated hypothesis H5 about the moderation of IT in this relationship. The main contributions of this thesis are: (1) the validation of the hypotheses, (2) the confirmation of the importance of IT in crisis contexts, and (3) the proposition of a future research agenda that emphasizes the need for a more proactive and interdisciplinary approach to the topic of Exogenous Shock. In the academic field, the research improves the theoretical understanding of Exogenous Shocks and Organizational Ambidexterity, proposing an innovative model that integrates IT as a moderator, enriching the literature and opening new research directions. In the organizational world, it offers practical insights for managers, highlighting the importance of resilience and adaptation through the strategic use of IT. Organizations are encouraged to adopt emerging technologies to improve data collection and analysis, facilitating rapid responses to Exogenous Shocks.